2016
DOI: 10.1186/s13613-016-0164-2
|View full text |Cite
|
Sign up to set email alerts
|

Toe-to-room temperature gradient correlates with tissue perfusion and predicts outcome in selected critically ill patients with severe infections

Abstract: BackgroundMicrocirculatory disorders leading to tissue hypoperfusion play a central role in the pathophysiology of organ failure in severe sepsis and septic shock. As microcirculatory disorders have been identified as strong predictive factors of unfavourable outcome, there is a need to develop accurate parameters at the bedside to evaluate tissue perfusion. We evaluated whether different body temperature gradients could relate to sepsis severity and could predict outcome in critically ill patients with severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
54
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 33 publications
1
54
0
2
Order By: Relevance
“…Despite tight inclusion parameters resulting in a relatively small sample for analysis, this study provides evidence of 24‐h rhythmicity disruption in a cohort of patients in an ICU, in line with studies over the past three decades examining circadian deregulation in ICU patients (Brainard et al, ; Madrid‐Navarro et al, ). Indeed, the rhythms of the parameters included in this study are used as predictors of mortality rates in patients in the ICU (Bourcier et al, ). The timing of exposure, as well as the quantum and rhythm of exposure, has been shown in previous studies to be key.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite tight inclusion parameters resulting in a relatively small sample for analysis, this study provides evidence of 24‐h rhythmicity disruption in a cohort of patients in an ICU, in line with studies over the past three decades examining circadian deregulation in ICU patients (Brainard et al, ; Madrid‐Navarro et al, ). Indeed, the rhythms of the parameters included in this study are used as predictors of mortality rates in patients in the ICU (Bourcier et al, ). The timing of exposure, as well as the quantum and rhythm of exposure, has been shown in previous studies to be key.…”
Section: Discussionmentioning
confidence: 99%
“…These parameters are continuously measured and monitored during the normal course of operation of most ICUs and are used as predictors of mortality rates in patients in ICUs. Their 24‐h rhythm can be altered by the influence of light (Bourcier et al, ; McKenna et al, ). This study investigated the potential role differential exposure to natural light in an ICU setting may play.…”
Section: Aims and Objectives Of The Studymentioning
confidence: 99%
“…Studying patients with septic AKI, Lara et al found that abnormal CRT in 95 septic patients with hyperlactatemia was associated with the need for RRT . Bourcier et al evaluated temperature gradients as proxy for tissue perfusion and found that it was associated with urine output in 40 critically ill patients with sepsis . Similarly, in our model subjectively cold temperature was associated with AKI.…”
Section: Discussionmentioning
confidence: 57%
“…We did not include patients with dark skin because CRT was difficult measure. It would be interesting to test the prognosis value of a score combining lactate and cardiovascular SOFA alone, or in association with other validated clinical parameters of peripheral hypoperfusion such as central-to-toe temperature difference [50]. As we could not include sessions performed in extreme emergency because data could not be recorded before the beginning of intermittent hemodialysis, IHI incidence was probably underestimated.…”
Section: Discussionmentioning
confidence: 99%